Rewiring Humanism: Review of Beastly Modernisms: The Figure of the Animal in Modernist Literature and Culture, edited by Saskia McCracken and Alex Goody - Sen, Anushka (Humanimalia, 2023)
Review of: Saskia McCracken and Alex Goody, eds., Beastly Modernisms: The Figure of the Animal in Modernist Literature and Culture. Edinburgh: Edinburgh University Press, 2023. x + 306 pp. 11 illus. (7 in colour). £110.00 (hb)